The Role of Green-Synthesized Fe3O4/Ag Magnetic Nanoparticle Masses on the Specific Absorption Rate toward Magnetic Hyperthermia Applications - Dhel Prisca Daro Kowe; Mahardika Yoga Darmawan; Nurul Imani Istiqomah; Edi Suharyadi; Nur Aji Wibowo (JRST (Jurnal Riset Sains dan Teknologi), 2025)
With chemotherapy and radiation therapy being the most common cancer treatments today, there are questions about their effectiveness and risks.Therefore, an alternative method that does not have significant side effects is needed, such as magnetic hyperthermia therapy (HM).The mass of magnetic nanoparticles (MNP) and the coating of MNP as anti-cancer agents play a very important role in optimizing the HM method, characterized by the Specific Absorption Rate (SAR) value.This study examines the effect of the mass of iron oxide magnetic nanoparticles with a silver coating (Fe3O4/Ag) on the Specific Absorption Rate (SAR) value. MNP Fe3O4/Ag was synthesized using the green synthesis (GS) method with Moringa oleifera (MO) plant extract.The results of this study show that GS-NPM Fe3O4/Ag has a crystal size between 42.69 - 43.58 nm with a bandgap energy of 2.50 eV, and contains functional groups O-H, C-H, N-Ag, Fe-O, and Fe-O-Si.There was a temperature change in the NPM Fe3O4/Ag for all mass variations, ranging from 0°C to 14.2°C over a period of 600 seconds, using a frequency of 15 kHz and an alternating magnetic field amplitude of 150 Oe.This temperature change indicates that the greater the mass of the NPM sample, the higher the NPM temperature. The lowest and highest SAR values obtained, consecutively, were 0.43 W/g at a mass of Fe3O4/Ag 0.125 grams and 1.11 W/g at a mass of 0.025 grams.